Ascorbate Is a Primary Antioxidant in Mammals - Junichi Fujii; Tsukasa Osaki; Tomoki Bo (Molecules, 2022)
Ascorbate (vitamin C in primates) functions as a cofactor for a number of enzymatic reactions represented by prolyl hydroxylases and as an antioxidant due to its ability to donate electrons, which is mostly accomplished through non-enzymatic reaction in mammals. Ascorbate directly reacts with radical species and is converted to ascorbyl radical followed by dehydroascorbate. Ambiguities in physiological relevance of ascorbate observed during in vivo situations could be attributed in part to presence of other redox systems and the pro-oxidant properties of ascorbate. Most mammals are able to synthesize ascorbate from glucose, which is also considered to be an obstacle to verify its action. In addition to animals with natural deficiency in the ascorbate synthesis, such as guinea pigs and ODS rats, three strains of mice with genetic removal of the responsive genes (GULO, RGN, or AKR1A) for the ascorbate synthesis have been established and are being used to investigate the physiological roles of ascorbate. Studies using these mice, along with ascorbate transporter (SVCT)-deficient mice, largely support its ability in protection against oxidative insults. While combined actions of ascorbate in regulating epigenetics and antioxidation appear to effectively prevent cancer development, pharmacological doses of ascorbate and dehydroascorbate may exert tumoricidal activity through redox-dependent mechanisms.